Long‐lived and heavier females give birth earlier in roe deer. Issue 3 (20th August 2013) - Plard, Floriane; Gaillard, Jean‐Michel; Coulson, Tim; Hewison, A. J. Mark; Delorme, Daniel; Warnant, Claude; Nilsen, Erlend B.; Bonenfant, Christophe
<x xml:space="preserve">Abstract</x> In seasonal environments, parturition of most vertebrates generally occurs within a short time‐window each year. This synchrony is generally interpreted as being adaptive, as early born young survive better over the critical season than late born young. Among large herbivores, the factors involved in driving among‐ and within‐individual variation in parturition date are poorly understood. We explored this question by analyzing the relative importance of attributes linked to female quality (longevity, median adult body mass and cohort), time‐dependent attributes linked to female condition (reproductive success the previous year, relative annual body mass and offspring cohort (year)), and age in shaping observed variation in parturition date of roe deer. A measure of quality combining the effects of female longevity and median adult body mass accounted for 11% of the observed among‐individual variation in parturition date. Females of 2 yr old give birth 5 d later than older females. Our study demonstrates that high quality (heavy and long‐lived) females give birth earlier than low quality females. Temporally variable attributes linked to female condition, such as reproductive success in the previous year and relative annual body mass, had no detectable influence on parturition date. We conclude that parturition date, a crucial determinant of reproductive success, is shaped by attributes linked to female quality rather than by time‐dependent attributes linked to female condition in income breeders (individuals that rely on current resource intake rather than on accumulated body reserves to offset the increased energy requirements due to reproduction) such as roe deer.